Smart cities : introducing digital innovation to cities - Gassmann, Oliver; Böhm, Jonas; Palmié, Maximilian (Emerald Publishing Limited, 2019)
Transformation through digital innovation is becoming an imperative for every city. The 'Smart City' concept promises to solve the most urgent queries of progressive urbanization in the area of mobility, energy, water supply, security, housing deprivation, and inclusion. Despite the exploitation of existing potential in lighthouse-cities that include Barcelona, London, Munich, Lyon, and Vienna, the less tenacious pursuit of smart city possibilities in the majority of municipalities has resulted in major discrepancies between leading smart cities and those that are less aspirational. Although the necessity of action is frequently recognized, an appropriate path of action remains obscure.Smart Cities: Introducing Digital Innovation to Cities offers answers, with clarifying examples, to questions that have remained unanswered for many cities. The book identifies and addresses the core elements and potential of smart cities, best practice methods and tools to be implemented, as well as how diverse stakeholders might be effectively integrated.Based on perennial international research in the field of smart cities, this book brings together the authors' collective experience in practice-based political, administrative, and economic projects to provide a common framework to guide and engage key stakeholders in the transformation and realization of smart cities.